Joint Optimization Design for Double Irregular IRS-Assisted Secure Communications - Wang, Jinlong; Feng, Ying; Zhou, Zhiquan; Wang, Chenxu; Jia, Shaobo; Zhang, Di (International Wireless Communications and Mobile Computing Conference (Online), 2025)
In this paper, we explore the utilization of double-irregular intelligent reflecting surfaces (IRS) for secure wireless transmissions, where "irregular" refers to the non-uniform arrangement of IRS elements on an expanded grid surface. The main objective is to maximize the secrecy rate by optimizing the arrangement of IRS micro-units and their phase shift matrices, subject to the transmission power constraint. Unlike previous research, this paper introduces the deployment of two IRSs with irregular distributions in a secure communication system, taking into account their reflective interaction. Additionally, the paper addresses both discrete and continuous phase considerations for IRS elements. Toward this end, we first propose a tabu search algorithm to simultaneously optimize the distribution matrices of both IRSs. Specifically, it employs alternating optimization techniques: for discrete phase adjustments, a cross-entropy method is applied, while for continuous phase shifts, a simulated annealing algorithm is used. Numerical results show that the proposed scheme significantly outperforms the regular scheme in enhancing the secrecy performance of the proposed system. Moreover, the suboptimal solutions found are closer to the optimal solution when leveraging irregular scheme.